Creating emotional value of the media in non-verbal business communications: a theoretical foundation: Creating emotional value of the media - Karkehabadi, Hamidreza; Delavar, Ali; ashayeri, hasan; Farhangi, Ali Akbar (Nordic Journal of Media Management, 2021)
The aim of this paper is to contribute to our understanding of the concept of “Media Emotional Value” in nonverbal business communication. An extensive review of the literature on nonverbal business communication and their theories was done. By studying three constructs, i.e. Emotional Content, Emotional intensity and Emotional valance related to “emotional media value” the authors identified an in-depth relationship between them and developed a model for nonverbal communication from costumers’ perspective. The relationship between the three constructs was developed to clarify how these factors shape the emotional media value. Additionally, an integrative model which is shaped by three constructs was developed. The construct of nonverbal business communication has received much attention in the last two decades. However, it has only focused on marketing managers’ views and has not been conceptualized satisfactorily. This article is an attempt to conceptualize nonverbal business communication from customers’ perspective